The Effect of Corn Leaf and Seaweed Flour Supplementation on The Carcass Cuts of Broiler Chickens Raised In Slatted Housing - Edo Robot; Suparmin Fathan; Ellen J. Saleh (International Journal of Technology and Education Research, 2026)
This research aims to determine the effect of corn leaf flour and seaweed flour on the carcass weight of broiler chickens raised in slatted pens. The study used 96 broiler chickens aged 2 weeks with a completely randomised design (CRD) consisting of 6 treatments and 4 replicates. The treatments included commercial feed (P0), 10% corn leaf meal (P1), 10% seaweed meal (P2), and combinations of corn leaf meal and seaweed meal (P3, P4, and P5). The variables observed included the weight of the wing, breast, thigh, and back pieces. The data were analysed using ANOVA and LSD post hoc tests. The results showed that the administration of corn leaf flour and seaweed had a significant effect (P<0.05) on all parts of the broiler chicken carcass. Treatment P0 produced the highest livestock weight, but treatment P1 produced relatively similar results. Increased use of seaweed tends to reduce carcass weight. It was concluded that the use of corn leaf flour up to 10% can still be used in broiler chicken rations without significantly reducing carcass weight.